The Effect of Duolingo Game as Extramural English Towards Students’ Vocabulary Mastery - Armiati, Armiati; Ayu, Citra; Asilestari, Putri; Sari, Nurhidayah (Universitas Pahlawan Tuanku Tambusai, 2025)
This experimental research was carried out in class X at SMA Muhammadiyah Bangkinang Kota. This research aims to determine the effect of duolingo game as extramural English towards students vocabulary Mastery at SMA Muhammadiyah Bangkinang. The research methodology uses a quasi-experimental design. The sample for this research consisted of 53 students, namely 29 students in class X Science two and 24 ostudents in class X Social. Data collection techniques include tests and documentation. Data were analyzed using SPSS 16. Based on the research results, it can be concluded that Duolingo Game can improve the Vocabulary Mastery of class X Science two students at SMA Muhammadiyah Bangkinang Kota as Extramural English . With an average posttest score of 86,42 and Paired T Test results with a significance level of 5% obtained Sig. (2-tailed) = 0,001 0,05 Therefore, it can be seen that ρ α, meaning that H0 is rejected and Ha is accepted. This proves that duolingo game has a significant effect on students' ability to improve English vocabulary in tenth grade.